Evaluation of Mangled Extremity Severity Score (MESS) as a Predictor of Lower Limb Amputation in Children with Trauma - Behdad, Saba; Rafiei, Mohammad Hadi; Taheri, Hadi; Behdad, Samin; Mohammadzadeh, Mahdi; Kiani, Gelare; Hosseinpour, Mehrdad (European Journal of Pediatric Surgery, 2012)
Background Management of the severely injured lower limb in children remains a challenge despite advances in surgical techniques. Models that predict the risk of lower limb trauma patients are designed to provide an estimation of the probability of limb salvage. In this study, we validate Mangled Extremity Syndrome Index (Mangled Extremity Severity Score [MESS]) by measurement of its discrimination in children.Materials and Methods From September 2009 to 2010, we collected the hospital records of all children who presented with lower extremity long bone open fractures. The inclusion criteria were I grade, II B, III C open fractures, severe injury to three of four organ systems, and severe injury to two of four organ systems with minor injury to two of four systems that require surgical interventions. Severity of limb injury was measured using MESS. Patients were followed up for 1 year. The discrimination of MESS model in differentiating of outcome in patients was assessed by calculating the area under the receiver operator characteristic plot.Results We evaluated 200 children referred consecutively to our center. The mean MESS in the amputation group was 7.5 ± 1.59 versus 6.4 ± 2.02 in the limb salvage group (p = 0.04). Amputation rate was 7.5% (n = 15). Percentages of skeletal/soft-tissue injury was different between groups (p = 0.0001). Children in the amputation group showed more tissue injury compared with limb salvage group. The best clinical discriminator power was calculated as MESS ≥ 6.5 (sensitivity = 73%, specificity = 54%).Conclusion We assumed that patients with a high risk of amputation can be identified early, and specific measures can be implemented immediately by using MESS with threshold of 6.5.
Keywords: Mangled Extremity Severity Score; trauma; children